2013
DOI: 10.11646/phytotaxa.98.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bituminaria basaltica</i> (Fabaceae), a new species from Italy

Abstract: Bituminaria basaltica is described and illustrated from Filicudi, an islet of the Aeolian Archipelago (Sicily, Italy). This new species, belonging to a small genus of Fabaceae occurring in the Mediterranean region and the Canary Islands, is morphologically distinct from the other taxa in the following features: leaf shape and size, inflorescence size, petal colour, size and shape of flowers, pods and seeds. Its relationships with the known species of Bituminaria are examined and a key to the genus is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
10
2
1
Order By: Relevance
“…Minissale et al. () reported that basal leaf petiole length never exceeded 13 cm in B. bituminosa populations from Sicily, while our study showed slightly higher values, up to 13.8 cm. The same author observed that basal leaf length in B. morisiana never exceeded 4.2 cm, whereas we found leaf lengths up to 5.2 cm.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Minissale et al. () reported that basal leaf petiole length never exceeded 13 cm in B. bituminosa populations from Sicily, while our study showed slightly higher values, up to 13.8 cm. The same author observed that basal leaf length in B. morisiana never exceeded 4.2 cm, whereas we found leaf lengths up to 5.2 cm.…”
Section: Discussioncontrasting
confidence: 73%
“…Nevertheless, the genetic basis of B. bituminosa is far from being fully explored. In B. morisiana, there is almost no characterization for agronomic performance, although some data are available for morphological traits (Minissale, Brullo, Brullo, Giusso Del Galdo, & Sciandrello, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The seed testa sculptures of Bituminaria were investigated by Minissale et al (2013), Giusso et al (2015), Brullo et al (2016) and Bogdanović et al (2016), who highlighted the systematic relevance of these features providing additional information in order to discriminate among the allied species. In particular, the species hitherto examined are B. bituminosa , B. palaestina , B. kyreniae , B. basaltica and B. plumosa , which are characterized by different patterns of seed testa.…”
Section: Species Treatmentmentioning
confidence: 99%
“…These speciation processes have been active in the genus Bituminaria which is represented by eight distinct species (Stirton 1981, Greuter et al 1989, Minissale et al 2013, Giusso et al 2015, Brullo et al 2016; Bogdanović et al 2016): B. bituminosa (L.) C.H. Stirt., B. morisiana (Pignatti & Metlesics) Greuter, B. flaccida (Nábělek) Greuter, B. basaltica Miniss., C. Brullo, Brullo, Giusso & Sciandr., B. kyreniae Giusso, C. Brullo, Brullo, Cambria & Miniss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation